2022
DOI: 10.3310/wpng1013
|View full text |Cite
|
Sign up to set email alerts
|

Developing programme theories of leadership for integrated health and social care teams and systems: a realist synthesis

Abstract: Background As the organisation of health and social care in England moves rapidly towards greater integration, the resulting systems and teams will require distinctive leadership. However, little is known about how the effective leadership of these teams and systems can be supported and improved. In particular, there is relatively little understanding of how effective leadership across integrated care teams and systems may be enacted, the contexts in which this might take place and the subseq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 436 publications
1
10
0
Order By: Relevance
“…The subtheme of evaluation methods acted as a key barrier to integrated care; seven review articles found insufficient evidence of evaluation due to heterogeneity within social enterprises, contexts within which they operated and the wide variety of health impacts ( 28 , 34 , 43 , 47 , 49 , 51 , 52 ), as described:…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The subtheme of evaluation methods acted as a key barrier to integrated care; seven review articles found insufficient evidence of evaluation due to heterogeneity within social enterprises, contexts within which they operated and the wide variety of health impacts ( 28 , 34 , 43 , 47 , 49 , 51 , 52 ), as described:…”
Section: Resultsmentioning
confidence: 99%
“…The need for this to be managed, or at least kept at bay, by clarity of message from those in positions of authority is another natural response to uncertainty. The difficulty with which this is genuinely provided by leadership, who are expected to recognize these hidden, embedded complexities and offer communication that is both clear and mindful of this is, therefore, considerable [( 51 ), p. 65].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This involves continuous learning and fostering an adaptive learning culture (Charles et al, 2018;Hendry et al, 2021 Working Together Integrated care leadership involves tackling complex 'wicked' problems and managing conflicts (Hulks et al, 2017;Social Care Institute for Excellence, 2018). Leaders must collaborate, share power, and use distributed leadership approaches (Aunger, Millar, Rafferty, Mannion, et al, 2022;Baylis and Trimble, 2018;Harris et al, 2022;Miller and Stein, 2020). Clear governance structures and data sharing are crucial for managing risk and decision-making (Booth-Smith, 2017;Cheng and Catallo, 2019;Harris et al, 2022).…”
Section: Individual Reflectionmentioning
confidence: 99%
“…Trust fosters collaboration and understanding of partners' motivations (Deffenbaugh, 2018;Ham, 2022;Harris et al, 2022).…”
Section: Relationships and Trustmentioning
confidence: 99%